Toward understanding the dynamics of land change in Latin America : potential utility of a resilience approach for building archetypes of landsystems change - Rocha, Juan C. (2019)
Fil: Rocha, Juan C. Stockholm University. Stockholm Resilience Centre. Stockholm, Suecia.